2014
DOI: 10.1208/s12249-014-0139-2
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation in Nanoparticles Improves Anti-cancer Efficacy of Carboplatin

Abstract: Poor cellular uptake contributes to high dose requirement and limited therapeutic efficacy of the platinum-based anticancer drug carboplatin. Delivery systems that can improve the cellular accumulation of carboplatin will, therefore, likely improve its therapeutic potential. The objective of this study was to evaluate nanoparticles composed of the biodegradable polymer, poly(D, L-lactide-co-glycolide), for carboplatin delivery to tumor cells. Carboplatin-loaded nanoparticles were formulated by double emulsion-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 37 publications
(42 reference statements)
1
16
0
3
Order By: Relevance
“…We initially optimized the conditions for nanoparticle loading in MSCs by evaluating the effect of dose of nanoparticles and the duration of incubation. These studies suggested that the maximal uptake of nanoparticles occurred after incubation with 100 μg/ml of nanoparticles for 4-6 h. Similar to what has been reported earlier in other cells [32], nanoparticles were found co-localized in the lysosomes (yellow) and also present free in the cytosol (green) (Supplementary Fig. 4).…”
Section: Discussionsupporting
confidence: 89%
“…We initially optimized the conditions for nanoparticle loading in MSCs by evaluating the effect of dose of nanoparticles and the duration of incubation. These studies suggested that the maximal uptake of nanoparticles occurred after incubation with 100 μg/ml of nanoparticles for 4-6 h. Similar to what has been reported earlier in other cells [32], nanoparticles were found co-localized in the lysosomes (yellow) and also present free in the cytosol (green) (Supplementary Fig. 4).…”
Section: Discussionsupporting
confidence: 89%
“…However, the potential of MSC to home toward the site of injury has exploited them as suitable tools to carry nanomaterials (mainly nanoparticles) for diagnostic and therapeutic purposes [115,116]. For example, the use of fluorescent/magnetic nanoparticles has improved the efficacy of stem cell-based therapies.…”
Section: Nanoparticles Labeled Cells As Therapeutic and Diagnostic Toolsmentioning
confidence: 99%
“…56 Moreover, NP formulations of carboplatin compounds are capable of providing controlled release of the drug for more than a week. 69 Although sustained release can be achieved through numerous biomaterial formulation strategies, NPs can be designed to enable brain-penetration and tumor targeting, 48,70 potentially improving treatment for invasive brain tumors, like GBM. Furthermore, free platinum drugs have a limited half-life in most tissues.…”
Section: Controlled and Sustained Drug Releasementioning
confidence: 99%